hubungan paritas dan usia - Devita Febriani Putri; Nurhaida Widiani; Debi Arivo (Holistik Jurnal Kesehatan, 2019)
TRANSOVARIAL TRANSMISSION OF DENV IN AEDES AEGYPTI Background: Transovarial transmission of dengue virus in Aedes aegypti mosquitoes is a vertical transmission of dengue virus infection in female Ae. aegypti mosquitoes to the offspring. The phenomenon of transovarial dengue virus transmission in Dengue Hemorrhagic Fever (DHF) vectors has been proven by laboratory and nature, which indicates the transovarial transmission of dengue virus has an important role in maintaining the dengue epidemic. DHF vector control especially Ae. aegypti mosquitoes is an effective method of stopping transmission and expansion of dengue cases.Purpose: This scientific article aims to understand the spread of dengue virus transovarially in dengue mosquito vectors, and its relation to the prediction of outbreak dengue cases as information on DHF vector surveillance so that it can make the appropriate control program.Methods: Collecting several scientific articles to obtain information on the studies that have been done and summarizing the results of the study.Results: Several result of study are proving that transovarial transmission of dengue virus in Aedes spp. mosquitoes  can predict dengue outbreaks case by monitoring the stadium immature Aedes sp., but it need further comprehension statistically about occurrence of dengue outbreaks and the increasing of dengue virus infections in immature stadium of mosquitoes.Discussion: Transovarial transmission rates from Ae. aegypti mosquito sample obtained from nature may be lower than in the laboratory, because laboratory condition can be controlled in accordande with the development of viruses in mosquito bodies. The dengue virus is proven to be able to spread between stages from eggs, larvae, pupae to imago and Ae. aegypti mosquitoes can act as reservoirs for  dengue virus until the 7th progeni.Conclusion: Dispersion dengue virus through transovarial in Ae. aegypti mosquito playing important role in viruses maintained in nature during absence of viremic vertebrata host or when the climate condition are not favorable for that viruses. Continuous monitoring of Ae. aegypti mosquitoes population vector related the early detection of virus circulation may contribute to the prediction models for dengue outbreaks, so that DHF control can be more effective.Pendahuluan: Penularan virus dengue secara transovarial pada nyamuk Aedes aegypti adalah transmisi secara vertikal dari nyamuk Ae. aegypti betina yang infektif virus dengue kepada keturunannya. Fenomena penularan transovarial virus dengue pada vektor Demam Berdarah Dengue (DBD) telah banyak dibuktikan skala laboratorium dan secara natural di alam, yang mengindikasikan penularan transovarial virus dengue memiliki peranan penting dalam mempertahankan epidemik DBD. Pengendalian vektor DBD khususnya nyamuk Ae. aegypti merupakan salah satu metode efektif dalam menghentikan penularan dan perluasan kasus DBD.Tujuan: Studi ini untuk memahami penyebaran virus dengue secara transovarial  pada vektor nyamuk DBD, serta kaitannya  terhadap prediksi kasus luar biasa (KLB) DBD sebagai informasi surveilans vektor DBD sehingga dapat membuat program pengendalian yang tepat.Metode: Dengan mengumpulkan beberapa artikel ilmiah untuk mendapatkan informasi studi yang telah dilakukan sebelumnya dan membuat ringkasan dari hasil studi tersebut.Hasil: Beberapa studi membuktikan penelitian transovarial virus dengue pada nyamuk Aedes spp. dapat memprediksi kasus KLB DBD dengan cara memonitoring stadium immature Aedes sp., namun perlu dilakukan studi statistik lebih lanjut untuk membuktikan hubungan terjadinya KLB DBD dan meningkatnya infeksi virus dengue pada stadium immature nyamuk.Pembahasan: Angka infeksi penularan transovarial virus dengue dari sampel nyamuk Ae. aegypti yang didapatkan langsung dari alam lebih rendah dari skala laboratorium, dikarenakan kondisi laboratorium dapat dikendalikan sesuai dengan perkembangan virus ditubuh nyamuk. Virus dengue terbukti dapat menyebar antar stadium dari telur, larva, pupa, sampai imago dan nyamuk Ae. aegypti dapat menjadi reservoir virus dengue sampai progeni ke 7.Kesimpulan: Penyebaran virus dengue secara transovarial pada nyamuk Ae. aegypti berperan penting dalam mempertahankan keberadaan virus di alam khususnya dimana tidak ada hospes vertebrata yang viremik atau ketika  keadaan (kondisi iklim) yang tidak menguntungkan virus tersebut di alam. Pemantauan berkelanjutan pada vektor demam berdarah nyamuk Ae. aegypti terkait deteksi dini sirkulasi virus dengue dapat berkontribusi pada pengembangan model prediksi KLB DBD, sehingga pengendalian DBD dapat lebih efektif.